The statutory rape law in Malaysia: An analysis from shariah perspective - Nur Aina, Abdullah; Haneef, Sayed Sikandar Shah (Zes Rokman Resources, 2017)
Statutory rape law in Malaysia is not only problematic from the current social trend but is questionable from an Islamic law perspective. This paper argues for its exclusion in terms of application in the case of Muslims.